HUBUNGAN DUKUNGAN LAYANAN KESEHATAN DARI PERSEPSI IBU, BBLR, ASI EKSLUSIF DAN ASUPAN DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS ANAK AIR KOTA PADANG - Dezi Ilham; Maria Nova (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Stunting is a chronic malnutrition problem caused by insufficient intake of nutrients for a long time due to feeding that is not in accordance with nutritional needs. The purpose of this study was to determine the relationship of health care support from the perception of mothers, LBW, exclusive breastfeeding, and intake with the incidence of stunting in toddlers in the work area of the Air Child Health Center in Padang City in 2021. This type of research is observational with a cross sectional research design. The population is 3,221 people, the research sample is 97 people using stratified random sampling technique. The data collected includes height with a digital height measuring device (digital wireless), Questionnaire, SQ FFQ. Univariate statistical test results show that stunting toddlers have health service support from mothers' perceptions of less than 37%, low birth weight toddlers 6%, not exclusive breastfeeding 56%, calcium intake less 73%, phosphorus intake 74%, Iodine intake 71.1%, zinc intake 68 %. Bivariate results showed that there was no significant relationship between stunting and health care support (p=0.762), low birth weight (p= 0.183), exclusive breastfeeding (p= 0.658), phosphorus intake (p= 0.173), and a significant relationship between stunting incidence with calcium intake (p= 0.018), iodine intake (p= 0.017), zinc intake (p= 0.008). It is expected that families, especially mothers, can pay more attention to the food consumed by toddlers, not only providing foods that are liked by toddlers but also providing varied foods so that the nutritional needs of toddlers can be met thereby reducing the risk of stunting.